A robust bootstrap approach to the Hausman test in stationary panel data models - Helmut Herwartz; Michael H. Neumann (Kiel University, Department of Economics, 2007)
In panel data econometrics the Hausman test is of central importance to select an e?cient estimator of the models' slope parameters. When testing the null hypothesis of no correlation between unobserved heterogeneity and observable explanatory variables by means of the Hausman test model disturbances are typically assumed to be independent and identically distributed over the time and the cross section dimension. The test statistic lacks pivotalness in case the iid assumption is violated. GLS based variants of the test statistic are suitable to overcome the impact of nuisance parameters on the asymptotic distribution of the Hausman statistic. Such test statistics, however, also build upon strong homogeneity restrictions that might not be met by empirical data. We propose a bootstrap approach to specification testing in panel data models which is robust under cross sectional or time heteroskedasticity and inhomogeneous patterns of serial correlation. A Monte Carlo study shows that in small samples the bootstrap approach outperforms inference based on critical values that are taken from a X?-distribution.
Keywords: C12; C33; 330; Hausman test; random effects model; wild bootstrap; heteroskedasticity; Panel; Statistischer Test; Bootstrap-Verfahren; Robustes Verfahren; Theorie